1973
DOI: 10.1071/bi9730575
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Potentially Pathogenic Phytophthora and Pythium Spp. From Native Vegetation in Australia

Abstract: Soil and plant root samples from a variety of native forest habitats throughout Australia were examined for potentially pathogenic Pythium and Phytophthora spp. by lupin baiting.Those It is suggested that disease of native plant species normally attributed to Ph. cinnamomi could be caused by other Pythium and Phytophthora species, acting singly or alone, with or without Ph. cinnamomi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1973
1973
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…This analysis occurred 4 years after the original mating during which time the progeny had been subcultured four times on cornmeal agar. Zoospore production was modified from a method of Pratt and Heather (1973). We grew isolates on V8 agar (Hü berli et al, 1997) for 5-7 days and then cut 1-cm 2 sections of mycelium on agar from the growing edge and placed them in sterile 9-cm petri dishes.…”
Section: Analysis Of Zoospore Isolates From Sexual Progenymentioning
confidence: 99%
“…This analysis occurred 4 years after the original mating during which time the progeny had been subcultured four times on cornmeal agar. Zoospore production was modified from a method of Pratt and Heather (1973). We grew isolates on V8 agar (Hü berli et al, 1997) for 5-7 days and then cut 1-cm 2 sections of mycelium on agar from the growing edge and placed them in sterile 9-cm petri dishes.…”
Section: Analysis Of Zoospore Isolates From Sexual Progenymentioning
confidence: 99%
“…Both also possessed hyphal swellings of the type described by previous authors for P. drechsleri, although these were more common in the southern than in the northern ecotype. Isolates of both ecotypes produced a few apparently homothallic oospores on inoculum plugs and oogonia, oospores, and amphigynous antheridia were similar in size, shape, and colour in each ecotype (Pratt and Heather 1973). In addition, the parallelism of the growth response curves in the presence of copper sulphate, pyronin G, and malachite green is considered to support strongly the claim that the two groups of organisms are ecotypes of a single species, P. drechsleri.…”
Section: Discussionmentioning
confidence: 49%
“…This paper, together with that of Pratt and Heather (1973), presents the first demonstration of sub specific groups based on physiological rather than pathogenic criteria. The salient characteristics of the two ecotypes are summarized in Table 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is caused primarily by P. cinnamomi, probably the most destructive root pathogen in Australia. Some workers (Pratt and Heather 1973a, 1973b, Pratt et al 1974 have suggested that various oomycetous fungi, such as Pythium spp., and other Pytophthora spp., may be involved in the disease etiology of this dieback. However, Marks and Kassaby ( 197 4,and unpublished data) have tested the pathogenicity of six species of Pythium and ten species of Phytophthora, and found that only P. cinnamomi was capable of killing 4-month-old eucalypts.…”
Section: Diebacksmentioning
confidence: 99%